Optimal designs for dose-response models with restricted design spaces - Holger Dette; Stefanie Biedermann; Wei Zhu (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
In dose response studies, the dose range is often restricted due to concerns over drug toxicity and/or efficacy. We present restricted and unrestricted interval locally optimal designs with respect to a very general class of optimality criteria for estimating the underlying dose response curve. The underlying curve belongs to a diversified set of link functions suitable for the dose response studies and having a common canonical form. These include the fundamental binary response models – the logit and the probit as well as the skewed versions of these models. The results are illustrated through the re-design of a dose ranging trial conducted at the Merck Research Laboratories (Zeng and Zhu, 1997). This work is a generalization of the results of Dai and Zhu (2002) in terms of the design interval, the underlying dose response curve and the optimality criterion.
Keywords: 519; Binary response model; Dose ranging; Dose response; Link function; General Equivalence Theorem; Locally compound optimal design; Theorie